The relationship between work environment and employees’ job satisfaction at Institut Latihan Perindustrian Kuantan (ILP KUANTAN) / Nurul Jannah Abd Aziz - Abd Aziz, Nurul Jannah (2019)
This research examines the relationship between work environment and employees’ job satisfaction at Institut Latihan Perindustrian Kuantan (ILP Kuantan). The main problem existed in their workplace were relationship with co-workers and lack of communication skill. Literature reviewed has details about job satisfaction, job security, relationship with co-workers and work-life balance. The data was collected using questionnaire from 112 respondents of five departments at ILP Kuantan and was identified using census technique. The data was analysed using Statically Package for Social Science (SPSS) Version 23 and result showed a positive correlation exist between work environment and employees’ job satisfaction at ILP Kuantan. There were a significant weak and positive relationship between job security and employees’ job satisfaction (p=0.000, r=0.399). The relationship between co-workers and employees’ job satisfaction showed a significant weak and positive relationship (p=0.000, r=0.346) and relationship between work-life balance and employees’ job satisfaction was significant weak and positive (p=0.000, r=0.384). There were several limitation of the study and the researcher suggested for future research to include another work environment as independent variable as their study. It was recommend to conduct the study in the others industry